Pecking Orders Uses and Limitations - Wong, S. Godwin ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
An interest in the comparative quality and prestige of academic programs is illustrated by the number of recent rating studies. Most recently, ratings have been made of graduate programs in various fields. These studies are generally of four types: (1) those using subjective evaluation; (2) those using objective indicators; (3) those using a combination of objective indicators; and (4) those using other studies' results and ranking institutions with a combination of programs. The results may be useful to administrators and students in a number of ways. However, these limitations are found: the fact that alumni tend to rate their own institutions favorably, so the institution's size may affect ratings; the time lag between perception of programs and current qualtiy; ranking of only the top end of the scale; the age of the program or institution, and the resultant number of alumni in the field; and undue generalization about program quality. (MSE)
ERIC Note: Paper presented at the Annual Forum of the Association for Institutional Research (17th, Montreal, Quebec, May 1977).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Alumni; Curriculum Evaluation; Educational Quality; Evaluation Criteria; Evaluation Methods; Graduate Study; Higher Education; Objectivity; Program Evaluation; Rating Scales; Research Methodology; Validity; Speeches/Meeting Papers